sistem informasi SISTEM INFORMASI PADA PERSEDIAAN BARANG BERBASIS WEB DI FROZEN FOOD: SISTEM INFORMASI PADA PERSEDIAAN BARANG BERBASIS WEB DI FROZEN FOOD - Fauziah Fauziah (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
Frozen Food Store is a store engaged in the sale of processed frozen instant foods that are durable and easy to serve. Meat-based frozen food products currently vary widely in the market and are consumed quite a lot. Survey data conducted by the Ministry of Agriculture (2015) revealed a very rapid development in the consumption of processed meat at the national level. The average development of processed meat consumption annually is 10.28 percent. The results of another survey stated that the increase in consumption of sausages grew by an average of 4.46 percent per year. Frozen food products such as nuggets, meatballs and sausages are the most consumed processed meat products. The increasing consumer demand for frozen food has an impact on the increasing demand for meat, chicken and beef. Currently at the Affa Frozen Food Store, the data collection process for incoming goods still has many shortcomings, often goods go out and inventory stock is not recorded due to human error, so that data collection in the store is not optimal. . In order for the system to run optimally, it is recommended to use an inventory information system. The purpose of this inventory information system is to overcome the problems that often occur in the currently running system at the Frozen Food Store and be a good solution for companies to create a faster and more accurate system in managing inventory. Often the company has problems